2016
DOI: 10.2174/1567202613666160517122109
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume During Ischemic Stroke is a Potential Pro-inflammatory Biomarker in the Acute Phase and During Neurorehabilitation Not Directly Linked to Clinical Outcome

Abstract: The prognostic role of increased mean platelet volume (MPV), as an indicator of platelet activation and large, more reactive platelets, in clinical and functional outcome of ischemic stroke is still conflicting. Studies are not currently available on the association between MPV and stroke recovery after neurorehabilitation. The relationship between MPV and clinical and functional outcome measures was assessed in twenty-four patients in the acute phase of first-ever ischemic stroke, and before and after 8-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…We corresponded with authors for five studies, but data were not available. Therefore, 34 articles were included in the meta-analysis [10][11][12][13][14][15]. Three studies were carried out in the United States, 12 in Europe, ten in Asia, one in Africa, and eight studies were intercontinental.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We corresponded with authors for five studies, but data were not available. Therefore, 34 articles were included in the meta-analysis [10][11][12][13][14][15]. Three studies were carried out in the United States, 12 in Europe, ten in Asia, one in Africa, and eight studies were intercontinental.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors consider a possible use of MPV assessments as a potential biomarker of AS or as a prognostic marker in patients after AS [10,12]. An association of MPV with stroke is possibly due to higher platelet activity, aggregation, and turnover in patients with elevated MPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasting results have also been published. Ciancarelli et al found no relationship between MPV values at baseline and NIHSS and mRS at 2 months, but they revealed that MPV decreases following 8 weeks of neurorehabilitation 37. Ntaios et al described no significant difference in the frequency of minor strokes and good functional outcome at 3 and 12 months across MPV quartiles 38.…”
Section: Discussionmentioning
confidence: 99%
“…Ntaios et al evaluated the associations between MPV values and NIH Stroke Scale scores but did not detect any significant correlations [ 25 ]. In another recently published study, Ciancarelli et al reported that no significant correlation was found between MPV values and NIH Stroke Scale and MRS scores [ 26 ]. Chen et al, investigated thrombocyte microparticles and MPV values in 112 patients with AIS, in which patients were divided into two groups, as large artery occlusion, and small artery occlusion group, but in both groups, MPV was found to be increased [ 27 ].…”
Section: Discussionmentioning
confidence: 99%